Penafsiran Zamakhsyari Terhadap Ayat-Ayat Tentang Pernikahan - lestari, puput (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2018)
Interpretation of Singles Ulama Against Marriage Verses. This simple study focuses on the study of a cleric's thoughts on ayat al-quran. The purpose of the word Singles Ulama here is a Ulama who until the end of his life has never been married. In Arabic terms it is called ‘uzzab or in the current term is called Singles. In this study I took the figure of Ulama al-zzUzzab namely Zamakhsyari which was taken from the book Al-Ulama al-zzUzzab, Alladzina Aatsaru al-Ilm ‘ala al-Zaawaj by Abdul Fattah Abu Ghuddah as the object of research. Then I used his commentary, Al-Kasysyaf to find out how he interpreted the marriage verse. I have the basic assumption that one's singles will influence the style of interpretation, especially in the verse that leads to marriage.